Research and reflexivity: the discourse of female students completing teacher education. Issue 4 (4th July 2017) - Meierdirk, Charlotte
Abstract: This paper explores the concept of reflexivity and its changing role for both the researcher and participants. A phenomenology was carried out following three female student teachers through their teacher training and how they managed their multiple roles. Twelve semi-structured interviews were carried out over the academic year to investigate the changing nature of identity. The discourses of the students were analysed to reveal the equilibrium/ disequilibrium of the student teacher's identity and the impact on both the researcher and the researched.